Book Reviews. Issue 1 (1st March 2019) - Block, Geoffrey; James, Nathan; Perez, Natalia Alexis
All That Jazz: The Life and Times of the Musical 'Chicago', Ethan Mordden (2018)New York: Oxford University Press, 260 pp., ISBN 978-0-19065-180-0, h/bk, 29.95Big Deal: Bob Fosse and Dance in the American Musical, Kevin Winkler (2018)New York: Oxford University Press, 350 pp., ISBN 978-0-19933-679-1, h/bk, £19.99Choreographing Copyright: Race, Gender, and Intellectual Property Rights in American Dance, Anthea Kraut (2015)New York: Oxford University Press, 336 pp., ISBN: 978-0-19936-037-6, p/bk, 38.95